P22 Airways oscillometry in asthma diagnosis in treatment naive but symptomatic adults. (11th November 2022) - Hiza, M; Healy, L; Drake, S; Wang, R; Bennett, M; Wilmore, L; Sale, J; Tudge, R; Lowe, L; Kerry, G; Fowler, S; Murray, C; et al.
Abstract : There is no single gold standard test to diagnose asthma. Many patients struggle to perform forced expiratory manoeuvres such as spirometry. Airways Oscillometry (AO) is a test of small airway function which can be measured during normal tidal breathing. Although AO has been shown to differentiate between asthma and healthy controls, and between severe and mild disease, there is little information whether AO has a role in asthma diagnosis in symptomatic but treatment naïve adults. Methods: Between May 2019 and April 2022, adults with possible asthma (cough, wheeze, breathlessness, and/or chest tightness) were referred to the Rapid Access Diagnostics for Asthma (RADicA) study by GPs across Manchester. Assessment included clinical history, examination, lung physiology (spirometry, reversibility, FeNO, PEFv and bronchial challenge), skin prick testing, serum eosinophils before and after 6–8 weeks of inhaled fluticasone (250µg BD). An expert panel of respiratory clinicians who assigned a diagnosis of 'asthma 'or 'not asthma'. Pre-ICS treatment measurements of AO (R5, R20, R5 - R20, AX, Fres X5, X5 in, and X5 ex; THORASYS TremoFlo®), as absolute values and% predicted, were compared between asthma and not asthma. Results: 110 adults completed the study (mean age 36 years; 63.6% female), 68 (62%) asthma and 42 (38%) not asthma. Absolute values of all AO measurements were not different between asthma and not asthma (p>0.15). However, % predicted values R5 and R20 were both significantly higher in asthma compared to not asthma. Conclusion: Our findings suggest that R5 and R20 AO results (as% predicted) were higher amongst symptomatic adults who were subsequently diagnosed with asthma, compared to those with symptoms that were not asthma. Further research is needed to evaluate the role of AO in asthma diagnosis, in particular, thresholds.